Faktor - Faktor yang Mempengaruhi Praktik Penghindaran Pajak di Sektor Energi - Elsa Novika Nisa Puspita Dewi; Juli Ratnawati (Akuisisi : Jurnal Akuntansi, 2025)
This study aims to analyze the Factors Affecting Tax Avoidance Practices in the Energy Sector (BEI) in 2019-2023. Energy companies have a total of 331 companies with 199 data samples in this study. The research method uses a quantitative method and the analysis technique used is multiple linear regression analysis with the SPSS version 26 program. The results of the analysis show that Profitability has a significant negative effect, Leverage has a significant positive effect and Institutional Ownership has a significant negative effect on tax avoidance while Company Size does not have a significant effect on tax avoidance in the energy sector. Further research can add independent variables and increase the research period so that the results obtained will be more optimal.